Kemampuan Maturasi dan Fertilisasi Oosit Sapi yang Diseleksi Menggunakan Teknik Pewarnaan Brilliant Cresyl Blue (SELECTING MATURATION AND FERTILIZATION ABILITY OF BOVINE OOCYTES USING BRILLIANT CRESYL BLUE) - Muttaqin, Zultinur; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus (Jurnal Veteriner, 2015)
The objective of this study was to evaluate the use of brilliantcresyl blue (BCB) in selecting potentialbovine oocytes for maturation and fertilization in vitro. Brilliant cresyl blue (BCB) is a dye that can assessintracellular activity of glucose-6-phosphate dehydrogenase (G6PD), a synthesized enzyme in maturedoocytes. Oocytes were exposed to 26 ?M BCB diluted in modified Phosphate Buffer Saline (mPBS, PBS +10% Fetal Bovine Serum) for 90 minutes is 5% CO2 incubator at 390C. The oocytes were classified accordingto their cytoplasm coloration: oocytes with blue cytoplasm (BCB+) and unstained oocytes (BCB-). Oocytesof the control group were incubated shortly after morphological selection without being exposed to BCB.Afterwards, all groups of oocytes (BCB+, BCB-, and control) were matured and fertilized in vitro. Maturedoocytes were those oocytes that reach metaphase II after 24 hours culturing; whereas oocytes showing twoor more pronuclei at 14 hours post incubation were classified as fertilized oocytes. The nuclear maturationrate was significantly (P<0.05) higher in BCB+ group (78.7% ± 0.41) than the BCB- group (33.3% ± 0.13).However, there was no significance difference (P>0.05) between the BCB+ and the control group (77.1% ±0.32). The fertilization rate was significantly higher (P<0.05) in the BCB+ group (30.5% ± 0.04) comparedto the BCB- (13.6%±0.03) and control group (23.6% ± 0.05). In conclusion, BCB staining of bovine oocytesprior in vitro maturation could be used in selecting potential developing oocytes.
Keywords: oocytes, brilliant cresyl blue, maturation, fertilization